Health and sustainable development: an analysis of 20 European voluntary national reviews. (March 2020) - Bickler, G.; Morton, S.; Menne, B.
Abstract: Objectives: United Nations member states agreed Agenda 2030 and the Sustainable Development Goals (SDGs) in 2015. Countries report their progress through Voluntary National Reviews. In this paper, we look at the extent to which the World Health Organisation (WHO) Europe SDG Roadmap (the Roadmap) on Agenda 2030 implementation is reflected in the first 20 Voluntary National Reviews (VNRs) submitted from the WHO European region. In particular, we wanted to look at how integrated the three dimensions of sustainable development were, the identification of health co-benefits and potential-added value from the health sector. Study design: This was a semi-quantitative analysis of 20 VNRs using an ordinal scale (no evidence, limited evidence, good evidence). Results are presented as frequency tables by criteria and by country. Methods: We devised an assessment template consisting of 41 criteria based on the nine key areas and a selection of the proposed areas for action in the Roadmap. Each VNR was then assessed and scored against these criteria to produce country-specific and average scores for each of the nine key areas and the 25 measures we selected. Results: Countries generally have good evidence on key areas such as governance, monitoring, leaving no-one behind and multipartner cooperation. They have less evidence on the key areas of health determinants, healthy settings, health literacy and investing for health. Many countries link the economic and environmental dimensions of sustainable development but not the interplay with the social (health and well-being) dimension. Some countries specifically highlighted commitments to support developing nations but few recognised the impact of domestic policies on planetary boundaries or the health of future generations. Conclusions: We found little evidence that the health sector has had a major strategic influence on actions which affect wider determinants (or health co-benefits). The WHO Europe SDG Roadmap offers a means and an opportunity for redressing this weakness, but this may require health professionals to work within their communities across all three dimensions of sustainable development. Highlights: This analyses 20 Voluntary National Reviews of SDG implementation from across WHO Europe against the WHO Europe SDG Roadmap. They show fair evidence about governance, partnerships, leaving no-one behind and monitoring and evaluation. They contain little evidence on health determinants, healthy settings, health literacy and investment for health. The VNRs do link the economic and environmental dimensions of sustainable development but not these and the social dimension. The health sector has not influenced actions on wider determinants or health co-benefits but there are opportunities to do so.